2015
DOI: 10.1007/s00339-015-9405-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer regulation of hole defect graphene by nitrogen doping

Abstract: Using classical molecular dynamics simulation, we investigate the thermal transport properties of hole defect graphene nanoribbons (HD-GNRs) possing various doping concentration of nitrogen atoms. By changing the concentration of nitrogen atoms, we try to find an effective method to adjust the heat transfer of HD-GNRs. The results show that the existence of hole defect in graphene destroys the structural integrity of the GNRs, which causes great decrease in thermal conductivity. We detect that nitrogen doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…from 0.64 at% to 1.35 at% with the increase of melamine addition). The in-plane thermal conductivity of rGO-M films is positively correlated with the content of graphitic N. The results are consistent with previous reports [36]. Among the three forms of N atoms, graphitic N preserves the graphene lattice's symmetry and electron conjugation [47].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…from 0.64 at% to 1.35 at% with the increase of melamine addition). The in-plane thermal conductivity of rGO-M films is positively correlated with the content of graphitic N. The results are consistent with previous reports [36]. Among the three forms of N atoms, graphitic N preserves the graphene lattice's symmetry and electron conjugation [47].…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, melamine is also commonly used as precursor for preparing nitrogen-doped graphene [34,35]. Based on molecular dynamics simulation, it is found that N doping could mediate defects in the graphene, resulting in an enhancement of in-plane thermal conductivity of graphene [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Although current experiments provide some clues about the nano-structure of SiCN, it is still very difficult to ascertain the structure of nano-domains in molecular scale (Saha et al, 2005;Zhang et al, 2015). Atomistic simulation is quite useful on investigating nano-scale properties of materials, it was successfully used in simulation of nano-materials (Feng et al, 2014;Gong et al, 2015;Gou et al, 2015;Kroll, 2010;Liao et al, 2015aLiao et al, , 2015bLiu et al, 2015;Plimpton, 1995;Silvestre et al, 2012;Wang et al, 2015). In this work, molecular dynamics simulations with empirical potential were conducted to study the molecular structure of SiCN.…”
Section: Introductionmentioning
confidence: 99%